ACCOUNTING IN THE GRADUATE PROGRAM OF THE SOCIAL-SCIENCE STUDENT. - Beatty, Willard C. (The Accounting Review, 1941)
Abstract Research into many important problems requires an understanding of both economics and accounting. It cannot be supposed that a single course in accounting will provide an adequate background for all problems therefore accounting in the graduate program of the social science student may be made a part of the course. The function of such a course would be an exposition of the basic principles of accounting and as far as possible an attempt would be made to explore some of the similarities and differences between economics and accounting. Accounting has a limited appeal to students of history, sociology, and political science. Most of those enrolling in the course will be students of economics. Of these the greater part will already have had sufficient background to give them an insight and interest in the problems of economics and accounting not uniformly characteristic of sophomores and juniors. Most of them will already have had courses in money and banking, corporation finance investments, marketing, and statistics. In addition some understanding of theory may be expected.